Safety evaluation of cable barriers installation on rural highways in British Columbia. (17th February 2019) - El Esawey, Mohamed; Sowers, Caitlin; Sengupta, Joy; Jain, Raoul
Abstract: Objective: The objective of this study was to evaluate the safety effectiveness of cable barrier systems installation on rural highway sections in British Columbia, Canada. Methods: Data on police-attended serious collisions (injury + fatality) on a number of rural highway sections in British Columbia, Canada, were used in the analysis. An empirical Bayes (EB) approach was employed to ensure that the evaluation results were reliable and to account for the regression to the mean artifact. Safety performance functions (SPFs) were developed using data collected at similar sites. For both median cable barrier (MCB) and roadside cable barrier (RCB) sections, the evaluation was undertaken using all serious collisions, truck serious collisions, and off-road serious collisions. Results: For MCB sections, the evaluation results showed statistically significant reductions of 21.7, 53.8, and 34.8% in all serious collisions, truck serious collisions, and off-road left (ORL) combined with head-on (HO) serious collisions. For RCB sections, statistically significant reductions of 74.7, 100, and 100% were found in all serious collisions, truck serious collisions, and off-road right (ORR) serious collisions, respectively. The impact of the after period on the evaluation results was explored. It was found that the changes in safety become more stable using an after period of 2–5 years. Conclusions: Cable barriers were successful in reducing the frequency of serious collisions on provincial highways in British Columbia.